Nutritional Deficiency-Induced Bilateral Ocular Blindness in a Newborn Lamb: A Case Report - Asuku, S. O.; Bamanga, U. M.; Ali, R. I.; Peter, I. D.; Waziri, M. A. (Sahel Journal of Life Sciences FUDMA, 2025)
This report reveals a rarely reported occurrence of ocular blindness in a newborn lamb suspected to be due to nutritional deficiencies in a pregnant Ewe. It involved a 1-week-old lamb brought to Theriogenology Unit of the University of Maiduguri Veterinary Teaching Hospital (UM-VTH), Maiduguri with complaint of sudden vision loss, noticed by the client after five days that the lamb was delivered. Clinical examinations revealed that both the dam and the lamb were feeble, but without any neurologic signs. Ophthalmic evaluations of the lamb revealed corneal opacity of the two eyes and a complete bilateral vision loss. The client was unable to ascertain the possibility of intake of colostrums within the first few days of birth of the lamb. In the ewe, un-thriftiness, unstable gait and notable appearances of the skeletal ribs and paralumbar fossa region were observed. The lamb died within few hours after presentation at the hospital. Optic nerve lesions and injuries on the cranial bones were not found during the postmortem ophthalmic examination of the lamb’s eye. Nutritional improvement that involved placement of ewe on diets supplemented with essential macro-and-trace minerals during pregnancy was recommended as a preventive measure for future re-occurrence of the condition in the sheep flock.